Twin pregnancy complicated with bowel strangulation. (8th September 2014) - Wong, Tze Fang; Imai, Shunichi; Tomita, Masato
Abstract : A 31-year-old primigravida at 35 weeks of gestation with twins who had no prior abdominal surgical history presented with worsening nausea, vomiting and abdominal pain. Initial screening ruled out obstetrical causes that may threaten the pregnancy. Twelve hours after the onset of symptoms, a transabdominal ultrasound revealed abdominal free fluid. A CT scan confirmed strangulated ileus involving the small bowels. Owing to non-reassuring fetal status in one of the twins, an emergency caesarean section and subsequent laparotomy were performed. The first twin presenting with fetal distress had to be resuscitated postdelivery but recovered uneventfully and met all developmental milestones by 3 months of age. The mother had a strangulated small bowel that had to be resected. She had an uncomplicated postsurgical course and gained full bowel function prior to discharge from the hospital.